High-Q, low-mode-volume and multiresonant plasmonic nanoslit cavities fabricated by helium ion milling. Issue 36 (5th September 2018) - Chen, Kai; Razinskas, Gary; Vieker, Henning; Gross, Heiko; Wu, Xiaofei; Beyer, André; Gölzhäuser, Armin; Hecht, Bert
Abstract : Helium ion milling of chemically-synthesized micron-sized gold flakes is performed to fabricate ultra-narrow nanoslit cavities with a varying length and width down to 5 nm. Abstract : Helium ion milling of chemically-synthesized micron-sized gold flakes is performed to fabricate ultra-narrow nanoslit cavities with a varying length and width down to 5 nm. Their plasmon resonances are characterized by one-photon photoluminescence spectroscopy. The combination of fabrication based on single-crystalline gold and resonant modes with low radiative losses leads to remarkably high quality factors of up to 24. Multiple Fabry–Pérot-type resonances in the visible/near infrared spectral range are observed due to the achieved narrow slit widths and the resulting short effective wavelengths of nanoslit plasmons. These features make nanoslit cavities attractive for a range of applications such as surface-enhanced spectroscopy, ultrafast nano-optics and strong light–matter coupling.